2014
DOI: 10.1684/abc.2014.0962
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Y chromosome microdeletions in infertile Tunisian men

Abstract: Yq microdeletions are the leading genetic cause of male infertility and its detection in clinically relevant for appropriate genetic counseling. The objective of this study was to determine the frequency of Y microdeletion in a group of Tunisian infertile men and to compare the prevalence of these abnormalities with other countries and other Tunisian reported series. Totally, 105 Tunisian idiopathic infertile men (74 azoospermic and 31 severe oligozoospermic) were screened for the presence of Y chromosome micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 29 publications
3
6
1
Order By: Relevance
“…This result is similar to that described in Ng et al [ 12 ] and Imken et al [ 35 ] reports, but different to the results found in other reports [ 17 , 34 , 42 , 43 ]. Several studies have shown that AZFc deletion was the most common [ 22 , 39 , 40 ], and these results are in accordance with ours (14.12 %). However, other studies showed conflicting results [ 33 , 35 , 42 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This result is similar to that described in Ng et al [ 12 ] and Imken et al [ 35 ] reports, but different to the results found in other reports [ 17 , 34 , 42 , 43 ]. Several studies have shown that AZFc deletion was the most common [ 22 , 39 , 40 ], and these results are in accordance with ours (14.12 %). However, other studies showed conflicting results [ 33 , 35 , 42 , 44 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, sixteen patients among the 85 analyzed infertile men showed the presence of Y microdeletions (18.83 %). This frequency is in accordance to that found by Ghorbel et al (17.1 %) [ 21 ], Fayez et al (20.4 %) [ 22 ], Imken et al (3.15 %) [ 35 ] and El Oualid et al (3.83 %) [ 36 ], although our cohort of patients showed a higher frequency, and this may be due to the low number of patients ascertained as well as the high number of patients with Y microdeletions, but higher than that found in the Chinese population (6.4 %; 8.5 %; 9.1 %) [ 12 , 37 , 38 ] or other Arab populations (Kuwait (2.6 %) [ 33 ], Tunisia (2.7 % and 6.85 %) [ 39 , 40 ], Saudi Arabia (3.2 %) [ 41 ] and Egypt (4 %) [ 42 ]. However, the frequency found in this study was included in the range of frequencies of wide world (1–55 %) [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…After KS, AZF microdeletions in this study is are the most common genetic abnormality (5.5%) among our study groups after KS (11.2%), (Table 4). This result is within the previously reported range of 0.98% to 55.5% for infertile men in several studies [4,14,24,25,27,28,31,34,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] .…”
Section: Discussionsupporting
confidence: 91%
“…Genetic abnormalities have been generally considered to be a main risk factor of idiopathic NOA (Hamada et al ., ; Rayburn, ). Currently, the techniques of chromosomal analysis and Y chromosome microdeletion detection screening are valuable for clinical diagnosis and therapy of male infertility with azoospermia (Hammami et al ., ; Yuen et al ., ). But so far, the pathogenicity factors of more than 50% of azoospermia are still unknown (Zhang et al ., ).…”
Section: Discussionmentioning
confidence: 99%